English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

write answer without using negative exponents

(3y^2 t^8)(4t^-9 w^5 y^-1)(7w^-5)

2007-03-09 15:58:59 · 5 answers · asked by Anonymous in Science & Mathematics Mathematics

5 answers

(3y^2 t^8)(4t^-9 w^5 y^-1)(7w^-5) =
(3y^2*y^-1) (t^8*4t^-9) (w^5*7w^-5) =
3y*4t^-1*7w^0 =
3y*4t^-1*7 =
3*4*7*y/t =
84y / t

2007-03-09 16:12:39 · answer #1 · answered by Anonymous · 1 0

Multiply the whole thing by w^5 and t^9 and y^1. That will allow you to remove the negative exponents.

2007-03-10 00:03:48 · answer #2 · answered by jflinca 2 · 0 1

(3y^2 t^8)(4t^-9 w^5 y^-1)(7w^-5)
= (3y^2) (t^8) (4t^-9) (w^5) (y^-1) (7w^-5)
= (3y^2)(y^-1) x (t^8)(4t^-9) x (w^5)(7w^-5)
= (3y) x (4t^-1) x (7)
= (3)(4)(7)(y/t)
= 84y/t

2007-03-10 00:07:03 · answer #3 · answered by Adrianne G. 2 · 1 0

3y^2.t^8.(1/t^9).w^5.(1/y)(1/w^5)
=3y/28t
(cancelling w^5 in both numerator n denomenator,y in denomenator and y^2 in numerator gives y in the numerator,t^8in the numerator and t^9in the denomenator givest in the denomenator so the fraction is 3y/(4tx7)=3y/28t
which is the answer.....)

2007-03-10 00:12:18 · answer #4 · answered by amrita 2 · 0 1

This is what I come up with : (84 y)/ t

2007-03-10 00:12:59 · answer #5 · answered by tipp10 4 · 0 0

fedest.com, questions and answers